Correlation between Inflammatory Marker and Glycemic Control in Patients with Ischemic Heart Disease - Ahmed, Mohsin; Islam, Md Mesbahul; Rahman, Mohammad Arifur; Rubaiyat, Khandaker Abu; Khuda, CM Khudrate E; Ferdous, Kazi Abul Fazal; Das, Bikash Chandra; Linda, Sanoat Kalam (Bangladesh Heart Journal, 2018)
Background: Recent evidence suggests that inflammatory markers and poor glycemic control are significantly associated with the development of cardiovascular complications. The purpose of this study was to determine the association between inflammatory marker (CRP) and glycemic status (HbA1c) in ischemic heart disease patients. Method: This cross sectional study was performed on 668 patients of ischemic heart disease in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka, who underwent Coronary angiogram from January 2017 to December 2017. CRP value were divided into normal (<6 mg/L), borderline (6-10 mg/L) and high (>10 mg/L) and HbA1c was divided <6.5% and ≥6.5%. After performed Coronary angiography the extent of disease was divided into insignificant CAD of (<50% stenosis), significant CAD considered as >50% stenosis and single vessel, double vessel, triple vessel CAD and normal coronaries. The relationship between CRP with HbA1c was analyzed by Chi square test. ANOVA test was used to analyze the continuous variables, shown with mean and standard deviation. Pearson’s correlation coefficient was used to test the relationship between CRP and HbA1c in CAD patients. p value <0.05 was considered as statistically significant. Result: Most (65.0%) of the patients belonged to age 41-60 years. The mean age was found 51.4±10.7 years. Majority (82.3%) of patients were male. Among risk factors, highest (40.0%) patients had hypertension followed by 209 (31.3%) diabetes mellitus and 204 (30.5%) smoker. Positive correlation was found (r=0.220, p= 0.001) between HbA1c with CRP in CAD patients. High CRP was found 138(38.4%) in <6.5% HbA1c and 187(60.5%) in ≥6.5 percent HbA1c. The difference was statistically significant (p<0.05). Multi variable logistic regression was found high HbA1c, high CRP and diabetes mellitus were statistically significant (p<0.05) in severe CAD (Double and triple vessel) patient. Conclusion: Positive correlation was found between serum levels of CRP and HbA1c in CAD patients. Thus, aiming at good glycemic control and estimation of serum CRP levels will possibly be of help in planning early intervention, thereby preventing further complications which in turn may help preserve cardiac functions in ischemic heart disease patients. Bangladesh Heart Journal 2018; 33(2) : 100-105